Prevalence of Social Anxiety and Body Image Dissatisfaction and Its Impact on Quality of Life of Medical Students- A Cross-Sectional Observational Study - Dharani. E, Dharani. E; Chitra. S, Chitra. S; RS, Shreenithy. (Journal of Neonatal Surgery, 2025)
Background: Medical students face significant psychological stress due to academic pressure, limited leisure time, and adaptation to the medical environment. Social Anxiety Disorder (SAD) and Body Image Dissatisfaction (BID) are common in this population and may impact their mental health and overall quality of life. Aim: To estimate the prevalence of social anxiety and body image dissatisfaction and assess their impact on the quality of life of medical students. Materials and Methods: A cross-sectional study was conducted among MBBS students at Vinayaka Mission’s Kirupananda Variyar Medical College, Salem, over five months from February 2024 to September 2024. A total of 365 students aged 18-25 years were recruited through random sampling. Participants completed validated tools, including the Liebowitz Social Anxiety Scale (LSAS), Body Self-Image Questionnaire (BSQ), and Mental Health Quality of Life Scale (MHQoLS-7D). Data analysis was performed using SPSS 26.0, with descriptive statistics, independent t-tests, and chi-square tests applied, the significance level of p<0.05. Results: The study found that 79.5% of students reported no social anxiety, 15.1% had mild social discomfort, 3.3% had moderate social phobia, and 2.2% had marked social phobia. Regarding BID, 63.8% of participants reported no concern, while 18.1% had mild concern, 9.6% moderate, and 8.5% marked concern. There was a statistically significant negative correlation between social anxiety and mental health quality of life (R=-0.440, p=0.001), as well as between body image dissatisfaction and quality of life (R=-0.486, p=0.001), indicating that higher levels of social anxiety and body dissatisfaction were associated with lower quality of life. Conclusion: A significant proportion of medical students experience social anxiety and body image dissatisfaction, which negatively impact their quality of life. Targeted psychological support and mental health interventions are necessary to improve well-being and academic performance in this population.